Incidence of bone tumors and tumor like lesions at a tertiary centre - a study of 64 cases - Verma, Nidhi; Tyagi, Amit; Singh, Preeti; Tyagi, Meenakshi; Rathi, Monika; Sharma, S. P. (International Journal of Research in Medical Sciences, 2018)
Background: Primary bone tumors are uncommon lesions constituting less than 1% of all cancers. Although open biopsy has high accuracy, it increases risk of tumor dissemination in patients with highly malignant tumors. FNAC eliminates the complications that may occur in surgical procedures and also gives quick results. This study was conducted to determine the spectrum and demographic characteristics of bone tumors and tumor like lesions at a tertiary care centre in western Uttar Pradesh and also to assess the role of FNAC in their diagnosis. Methods: This is a three-year, retrospective as well as a prospective study done on a total of 64 cases. All the cases were subjected to detailed history, physical examination and radiological investigations. FNAC smears were stained with Giemsa and Papanicolaou stain. H and E staining was done for histopathology. Results: Mean age affected was 26 years. Male-female ratio was 2.8:1. Out of total 64 cases of bone tumors and tumor like lesions, maximum was chondrogenic tumors (17; 26.56%), followed by osteogenic tumors (15; 23.44%). Osteochondroma (08; 47.06%), Osteosarcoma (07; 46.66%) and Aneurysmal bone cyst (04; 50.0%) were the most common chondrogenic tumor, osteogenic tumor and tumor like lesion respectively. The most common bone affected was tibia (16; 25.0%), followed by femur (15; 23.4%). Sensitivity and specificity of FNAC as a diagnostic modality were 90.0% and 91.67% respectively. Conclusions: A good correlation is observed between cytological and histological diagnoses which implies that FNAC can be used as a preliminary diagnostic approach to bone tumors, although histopathology remains the gold standard.